P08 Spontaneous bacterial peritonitis prophylaxis: reducing the incidence of c difficile infection. (6th September 2011) - Jafferbhoy, H; Miller, M H; Shekar, C; Lockhart, M; Dillon, J F
Abstract : Introduction: Spontaneous bacterial peritonitis is a serious and life-threatening complication of cirrhosis, especially common in hospitalised patients. Antibiotic prophylaxis is effective but can lead to an increased incidence of hospital-acquired infections such as Clostridium difficle . Aim: We evaluated whether two alternative prophylaxis agents were equally efficacious in preventing SBP, and the impact on risk of C difficile infection. Method: A consecutive, cohort study of hospitalised patients with cirrhosis and ascites, over a 3-year period in a tertiary hospital. In the first cohort (2007–2009), ascitic patients requiring prophylaxis received Norfloxacin 400 mg/d during their hospital admission. In the second cohort (2009–2010) patients received prophylactic Co-trimoxazole 960 mg/d during their hospital admission. Data were extracted by case note review and the two cohorts compared. Results: 174 patients admitted during 2007–2010 accounted for 231 hospital episodes with ascites. The Norfloxacin group had 154 episodes and the Co-trimoxazole group had 77. The mean age of the cohort was 57.4 years (SD 12.4) and 62% were male. Alcoholic cirrhosis was the major aetiology accounting for 79% of cases. The mean Child-Pugh and UKELD scores were 10.7 and 54 respectively. The overall incidence of SBP in our cohort was 19%. Abstract P08 table 1 demonstrates that the incidence of hospital acquired SBP, prophylaxis failure and mortality was not statistically different between the two therapies. However, selective bowel sterilisation with Co-trimoxazole did not lead to an increase C difficle infection rate. Conclusion: Survival of cirrhotic patients with ascites is inversely related to severity of Liver disease, worsened with development of infections such as spontaneous bacterial peritonitis and C difficle . This study shows that Co-trimoxazole inpatient prophylaxis against SBP is as effective as quinolone based regimes, but has the advantage of a dramatic reduction in C difficle infection. At the same time the importance of measures like hand hygiene compliance, environmental cleanliness and strict policy of in hospital antibiotic prescribing cannot be underestimated.